Analisis Framing Pemberitaan Kasus Rafael Alun Trisambodo di Media Online CNN Indonesia.com dan Kompas.com - Simanjuntak, Putri Novita Sari; Abidin, Sholihul (LPPM Universitas Putera Batam, 2023)
Rafael Alun Trisambodo is a civil servant who has assets of IDR 56 billion. A fantastic figure for an echelonIII official so that these assets made Rafael in the public spotlight. Based on this, the Rafael Alun Trisambodocase went to the stage of investigation by the KPK. Furthermore, the KPK found strong evidence ofallegations of receiving gratuities and named Rafael as a suspect. This study aims to determine the realityof CNN Indonesia.com and Kompas.com media in framing news regarding the handling of the KPK in theRafael Alun Trisambodo case. This study uses Robert Entman's framing analysis with qualitative researchmethods. The results of the study found similarities and differences between CNN Indonesia.com andKompas.com in constructing reports on the case of Rafael Alun Trisambodo